2013
DOI: 10.1016/j.athoracsur.2013.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Blocks Fibrocyte Migration and Attenuates Bronchiolitis Obliterans in a Murine Model

Abstract: Background Fibrocytes are integral in the development of fibroproliferative disease. The CXCL12/CXCR4 chemokine axis has been shown to play a central role in fibrocyte migration and the development of bronchiolitis obliterans post lung transplantation. Inhibition of the mTOR (mammalian target of rapamycin) pathway with rapamycin has been shown to decrease expression of both CXCR4 and its receptor agonist, CXCL12. Thus, we hypothesize that rapamycin treatment would decrease fibrocyte trafficking into tracheal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In heterotopic tracheal transplant models, mesenchymal cells have been shown to be derived from the recipient rather than the donor, 29 and the fibrocyte population is being investigated. 27,28 Similar findings of recipient derivation of mesenchymal cells was suggested in an intrapulmonary tracheal transplant model of BO using immunofluorescent staining. 56 The contrary finding of the predominant donor origin of collagen Ieexpressing cells in murine lung allografts in the present study could reflect the investigation of fibrosis in a whole-lung allograft rather than in an isolated trachea.…”
Section: Discussionsupporting
confidence: 66%
“…In heterotopic tracheal transplant models, mesenchymal cells have been shown to be derived from the recipient rather than the donor, 29 and the fibrocyte population is being investigated. 27,28 Similar findings of recipient derivation of mesenchymal cells was suggested in an intrapulmonary tracheal transplant model of BO using immunofluorescent staining. 56 The contrary finding of the predominant donor origin of collagen Ieexpressing cells in murine lung allografts in the present study could reflect the investigation of fibrosis in a whole-lung allograft rather than in an isolated trachea.…”
Section: Discussionsupporting
confidence: 66%
“…The full mechanism of rapamycin's immunosuppression is still under exploration. When we study the effects of rapamycin on BO development through inhibiting fibrocytes recruitment (10) and promoting epithelial progenitor cell regeneration(11), an unexpected finding was seen that rapamycin significantly reduced luminal obliteration, but markedly increased cellular infiltration in the allografts on days 14 and 28. We and others have reported previously that the cellular infiltration was peaked on day 7, then the inflammatory cells gradually decreased to base levels (6, 7, 27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports showed that short course treatment of rapamycin, a macrocyclic triene antibiotic pro-drug, prevented development of BO through two different mechanisms in a HTT model: 1) reducing fibrocyte recruitment to the tracheal allografts(10); 2) protects against airway epithelium loss and promotes epithelial progenitor cells(11). During these studies, we appreciated that despite rapamycin significantly reduced BO development-; it simultaneously increased cell infiltration into the allografts.…”
Section: Introductionmentioning
confidence: 99%
“…We utilized a murine HTT model of bronchiolitis obliterans, as previously described [16, 21-23]. Briefly, donor mice were anesthetized and their trachea were removed via a midline cervical incision.…”
Section: Methodsmentioning
confidence: 99%
“…Rapamycin has both immunosuppressive and anti-fibrotic properties [15]. We have shown that rapamycin treatment prevents secondary loss of the epithelium and mitigates the development of BO in the HTT model [16]. Rapamycin treatment also reduces intra-tracheal levels of fibrocytes [16].…”
Section: Introductionmentioning
confidence: 99%